Squamous cell carcinoma (SCC) of the renal pelvis following chronic nephrolithiasis; presented with feature suggesting xanthogranulomatous pyelonephritis - Abdalla Ali Alzubier, Mosab; Eltyeb Ibrahim, Ahmed; Mahjoub Taha, Sami (International Journal of Medicine, 2020)
Background: Squamous cell carcinoma (SCC) which originated in the urothelium of the urological system is not uncommon; however, it is rare in the renal pelvis. Additionally, it is hard to be diagnosed without high clinical suspicion.Case summary: A-66-years old female presented with left loin pain for 6 years, hematuria, and fever for months. Examination revealed no abnormality apart from pallor and bimanually palpable left kidney. Her investigations showed normal renal function and anemia, Computer Topography for Kidney, Ureter, and Bladder (CT-KUB) revealed a large left renal pelvic stone with a hugely enlarged kidney with suspicion of xanthogranulomatous pyelonephritis (XGPN), with almost absent function of the left kidney in DTPA. She underwent Left trans-peritoneal radical nephrectomy. Post-operative histopathology result was moderately differentiated squamous cell carcinoma (T3, N0, M0). To our knowledge this was the first reported case in our hospital, we think that the treatment was fair putting in mind the poor prognosis of the condition and the difficulty in diagnosis.Conclusion: This case demonstrates renal pelvis SCC presented with radiological features suggestive of xanthogranulomatous pyelonephritis.Â Â